2019
DOI: 10.4178/epih.e2019016
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors contributing to the incidence and mortality of acute childhood poisoning in emergency department patients in Iran: a hospital-based case-control study

Abstract: OBJECTIVES: Since poisoning is one of the most important preventable factors contributing to the hospitalization and death of children who present to emergency departments, this study was carried out to investigate the risk factors contributing to the incidence and mortality of acute childhood poisoning.METHODS: This hospital-based case-control study included 243 cases and 489 controls, drawn from daily admissions to the emergency departments of the included hospitals according to the inclusion and exclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
19
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 21 publications
8
19
3
4
Order By: Relevance
“…Therapeutic drugs were the most common cause of poisoning in the present study which constituted about (32.69%). This was matched with studies conducted in Turkey [22] and in Iran [23] [24] where poisoning due to medications over-dose was found to be the most common cause of childhood poisoning.…”
Section: Discussionsupporting
confidence: 80%
“…Therapeutic drugs were the most common cause of poisoning in the present study which constituted about (32.69%). This was matched with studies conducted in Turkey [22] and in Iran [23] [24] where poisoning due to medications over-dose was found to be the most common cause of childhood poisoning.…”
Section: Discussionsupporting
confidence: 80%
“…Disfani HF et al . [ 19 ] observed that in 87.7% cases gastrointestinal poisoning was present but, in our study, only 15% cases had gastrointestinal involvement. 49.8% of their cases had poisoning related to medications which was only 11% in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, research that compares frequency of calls to PCs and visits to the ED among these subgroups may assist with targeted efforts to promote PC utilization when TE occurs. Consistent with other studies, 1,13,14 children ages 0-9 are at the highest risk for TE compared to other age groups. Numerous studies have attempted to understand and investigate the cause of this epidemiological finding.…”
Section: Lotfipour Et Alsupporting
confidence: 91%